Acutipetala gen. nov., a new genus of funnel-web spiders from northern Thailand (Araneae, Agelenidae) - Dankittipakul P. (2014)
A new funnel-web spider genus, Acutipetala gen. nov., is erected to accommodate two new agelenid species known to occur in evergreen forests of northern Thailand: Acutipetala octoginta sp. nov. (type species, ♀♂) and A. donglini sp. nov. (♀). The genus is established on the basis of the distinctive appearance of the genital structures, in which the median apophysis of the male palp is petal-shaped, sharply pointed, and strongly sclerotized, and the truncate embolus is short, originates subapically, and is provided with a hook-shaped apical portion. © 2008 Zoological Society of Japan.